??PHYSICO-CHEMICAL AND METAL COMPOSITION OF CALOPHYLLUM INOPHYLLUM SEED AND SEED OIL? ? ?Short Communication (Biological Sciences - PJSIR, 2000)
Calophyllum inophyllum Linn, is a beautiful ornamental treewith long stalked white flowers at the ends of the branches.Its glossy broad elliptic leaves with numerous parallel lateralveins are most distinctive. C. inophyllum belongs to Guttiferaewhich are trees or shrubs occurring chiefly in the tropics. Theyhave simple opposite leaves, often with translucent lines ordots. All of the Nigerian species yield resinous juice whenslashed and most of them have distinctly whorled branches(Keay et al 1966).